2012
DOI: 10.3858/emm.2012.44.5.035
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo bilobaextract (GbE) enhances the anti-atherogenic effect of cilostazol by inhibiting ROS generation

Abstract: In this study, the synergistic effect of 6-[4-(1-cyclohexyl-1H-tetrazol-5-yl) butoxy]-3,4-dihydro-2(1H)-quinolinone (cilostazol) and Ginkgo biloba extract (GbE) was examined in apolipoprotein E (ApoE) null mice. Co-treatment with GbE and cilostazol synergistically decreased reactive oxygen species (ROS) production in ApoE null mice fed a high-fat diet. Co-treatment resulted in a significantly decreased atherosclerotic lesion area compared to untreated ApoE mice. The inflammatory cytokines and adhesion molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…For example, it is widely used for the treatment of several neurological disorders for its anti-oxidant and anti-platelet properties [ 21 – 23 ]. EGb761 has anti-oxidant effects in cerebral and peripheral arterial diseases by inhibiting ROS generation [ 24 ]. Moreover, it has been recently reported that EGb761 has anti-proliferation and apoptosis-inducting effects in various cancers such as those of the pancreas and colon [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is widely used for the treatment of several neurological disorders for its anti-oxidant and anti-platelet properties [ 21 – 23 ]. EGb761 has anti-oxidant effects in cerebral and peripheral arterial diseases by inhibiting ROS generation [ 24 ]. Moreover, it has been recently reported that EGb761 has anti-proliferation and apoptosis-inducting effects in various cancers such as those of the pancreas and colon [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dies könnte für die Sekundärprävention relevant sein, und eine neuere In-vivo-Studie zeigte unter der Kombination von Cilostazol mit einem Gingkoextrakt einen additiven Effekt [46]. …”
Section: Diskussionunclassified
“…[8] Ginkgo biloba extracts that exert neuroprotective effects by complex mechanisms such as potent platelet-activating factor antagonism, increased blood fl ow, and free-radical scavenging have been used for cerebrovascular insuffi ciency, dementia, stroke, tinnitus, and others. [9][10][11] The combination of these two drugs has been documented to enhance antiplatelet/antithrombotic, [12] anti-atherogenic, [13] and neuroprotective effects [14] of each drug. The present study was designed to investigate the postexposure protective effects of renexin on hearing, the organ of Corti (OC), and MOC efferents against damage caused by noise.…”
Section: Introductionmentioning
confidence: 98%